INDEPENDENT COMMISSIONER’S EXISTENCE AND EXPERTISE INFLUENCES ON INDONESIAN RURAL BANK’S CREDIT PERFORMANCE - Nung Harjanto; Rahmawati Rahmawati (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
Although the BPR's growth rate is very good, most BPRs of 1,184 (68%) are with limited core capital (CC) of less than IDR 6 billions. One of the main problems with BPRs with core capital below IDR 6 billions is that the credit performances of those Indonesian Rural Banks tend to deteriorate. In the other hand, according to OJK in POJK No.4/POJK.03/2015, the existence of independent commissioner is only compulsory for BPRs with core capital IDR 50 billionss and above. This research is concentrated to the empirically analyze of the worsening cause of the lack of governance, especially the effects of the existence of independent commissioner and independent commissioner’s expertise on the credit performance of BPRs with core capital below IDR 50 billions. Using purposive sampling, the sample data are taken from BPRs in Central Java Province and Yogyakarta Special Region Province. The secondary data related to these research variables are processed and analyzed by cross-sectional linear regression using SPSS statistic software with a significance level of 5%. This research result shows that independent commissioners' existence and independent commissioner’s expertise have positive significant effects on the credit performance of BPRs with core capital below IDR 50 billions.Keywords: Credit Performance, Expertise, Internal Governance, Independent Commissioner, and Rural Bank